2009
DOI: 10.1038/hdy.2009.171
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of Atlantic salmon fry to freshwater infectious pancreatic necrosis is largely explained by a major QTL

Abstract: Infectious pancreatic necrosis (IPN) is a viral disease with a significant negative impact on the global aquaculture of Atlantic salmon. IPN outbreaks can occur during specific windows of both the freshwater and seawater stages of the salmon life cycle. Previous research has shown that a proportion of the variation seen in resistance to IPN is because of host genetics, and we have shown that major quantitative trait loci (QTL) affect IPN resistance at the seawater stage of production. In the current study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 20 publications
1
148
1
1
Order By: Relevance
“…A quantitative trait loci explaining a very large proportion of the genetic variation in IPN resistance has been detected in Atlantic salmon (Houston et al, 2009;Moen et al, 2009). In our study, evidence was found of significantly favourable genetic correlations of resistance to furunculosis in unvaccinated fish with resistance to both IPN and ISA (unvaccinated fish).…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative trait loci explaining a very large proportion of the genetic variation in IPN resistance has been detected in Atlantic salmon (Houston et al, 2009;Moen et al, 2009). In our study, evidence was found of significantly favourable genetic correlations of resistance to furunculosis in unvaccinated fish with resistance to both IPN and ISA (unvaccinated fish).…”
Section: Discussionmentioning
confidence: 99%
“…Aquaculture species are typically close to their wild ancestors and the relatively new selection and disease pressures in the farm environment raise the possibility that major-effect loci segregate within the populations. A successful example of QTL analyses applied to selective breeding is the case of infectious pancreatic necrosis resistance in Atlantic salmon, in which a major QTL explains the majority of the genetic variance for resistance (Houston et al, 2008;Houston et al, 2010;Moen et al, 2009) and has been demonstrated as a successful means of controlling the disease . Selected other examples of QTL-affecting resistance to disease include the cases of salmonid alphavirus (Gonen et al, 2015), ISAV (Moen et al, 2007), and Gyrodactylus salaris (Gilbey et al, 2006) in salmon, lymphocystis disease in Japanese flounder (Fuji et al, 2006), Bonamiosis in the European Flat Oyster (Lallias et al, 2009), and Flavobacterium psychrophilum in rainbow trout (Vallejo et al, 2014).…”
Section: Current Methods Of Breeding For Disease Resistancementioning
confidence: 99%
“…This QTL was confirmed in three other families. Several authors have reported QTLs for IPNV, and most show that the anti-IPNV loci are located on LG21 [37][38][39][40], indicating that rainbow trout and Atlantic salmon anti-IPNV QTLs may be evolutionarily conserved. The genetic effects of Atlantic salmon anti-IHN QTLs have been validated in other studies [41].…”
Section: Qtl For Disease Resistancementioning
confidence: 99%